PENGARUH RASIO PROFITABILITAS DAN RASIO LEVERAGE TERHADAP HARGA SAHAM PERUSAHAAN MANUFAKTUR DI BURSA EFEK INDONESIA - Arnanto, Zia; T, Sutrisno (Jurnal Ilmiah Mahasiswa FEB, 2016)
This research aimed to examine the effect of profitability ratio and leverage ratio to the stock price of Indonesia Stock Exchange (IDX) listed manufacturing companies. This research used sample from population of manufacturing companies that have been listed in the Stock Exchange from 2009 to 2012. There are 70 manufacturing companies obtained as samples using purposive sampling method. The types of data used are secondary data obtained from the Indonesian Stock Exchange and Indonesian Capital Market Directory (ICMD). The data collection technique used is the documentation technique. Multiple linear regression analysis is used to answer the research problem. The results of this research showed that Return on Assets (ROA) and Earning Per Share (EPS) have significant effects on stock prices, while the Debt to Equity Ratio (DER) has no significant effect on stock prices. Keywords: Profitability, leverage, return on asset (ROA), Earning Per Share (EPS), Debt to Equity Ratio (DER), stock price.